PENERAPAN MEDIA PEMBELAJARAN TARI (MENTARI) DI SEKOLAH INKLUSI DCC GLOBAL SCHOOL - Erina; Nabilla Kurnia Adzan; Susi Wedhaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of audiovisual-based dance learning media (Mentari) in an inclusive school at DCC Global School. The study employed a qualitative approach with primary data sources consisting of classroom teachers, assistant teachers, shadow teachers, and sixth-grade students, while secondary data were obtained from learning documents, teaching modules, Mentari videos, and learning activity documentation. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles and Huberman data analysis model, which includes data collection, data reduction, data display, and conclusion drawing. The results indicate that the audiovisual-based dance learning media (Mentari) functions as an effective stimulus in dance learning within an inclusive classroom. Clear movement visualization and appropriate musical accompaniment help students understand and imitate dance movements with greater confidence. Both regular students and students with special needs were able to participate in the learning process together with the support of teachers and shadow teachers. Students’ responses were reflected in increased participation, focus, and enthusiasm during the learning process. Reinforcement in the form of praise, guidance, and repeated practice provided by teachers was proven to strengthen students’ learning responses. The implementation of Mentari aligns with behavioristic theory, which emphasizes the relationship between stimulus, response, and reinforcement in supporting dance learning in inclusive classrooms.